Teaching mindfulness-based stress management techniques to medical learners through simulation - Smith, Stephanie; Griggs, Lauren; Rizutti, Franco; Horton, Joan; Brown, Allison; Kassam, Aliya (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Implication Statement: Acutely traumatic clinical events can exacerbate stress and burnout amongst healthcare providers. The Simulated Training for Resilience in Various Environments (STRIVE) course may provide a useful framework for medical educators to teach stress management skills to promote resilience amongst physician trainees. The course introduces the Big Four+ techniques (goal setting, visualization, self-talk, progressive muscular relaxation, attention control and tactical breathing) created by the Canadian Armed Forces using clinical scenarios. This framework can be easily adapted across other training contexts to equip future clinicians with a foundational skill set to optimize their response and recovery following critically stressful incidents.